Functional Characterization of Cryptococcal Genes: Then and Now - du Plooy, Lukas M.; Sebolai, Olihile M.; Pohl, Carolina H.; Albertyn, Jacobus (Frontiers in Microbiology, 2018)
Site-directed mutagenesis enables researchers to switch a gene of interest off for functional characterization of the gene. In the pathogenic yeasts, Cryptococcus neoformans and sister species C. deneoformans, this is almost exclusively achieved by introducing DNA into cells through either biolistic transformation or electroporation. The targeted gene is then disrupted by homologous recombination (HR) between the gene and the transforming DNA. Both techniques have downsides; biolistic transformation equipment is very expensive, limiting the use thereof to well-resourced laboratories, and HR occurs at extremely low frequencies in electroporated cells, making this method unappealing for gene targeting. Two research groups have recently obtained a much higher frequency of HR by utilizing CRISPR-Cas9. The Cas9 nuclease forms a double strand break in the targeted gene, which seems to stimulate HR. The less expensive electroporation technique can therefore be used to deliver the CRISPR-Cas9 components into cells to disrupt a gene of interest, but only if the CRISPR components can be maintained for long enough in cells to enable their expression. Maintenance of episomal DNA occurs readily in C. deneoformans, but only under certain conditions in C. neoformans. In addition, CRISPR-Cas9 allows gene complementation in order to fulfil Falkow’s molecular Koch’s postulates and the Cas9 nuclease can also be modified, such as with a fluorophore, to extent the current gene characterization toolbox – taking cryptococcal molecular biology from a struggling past to a bright future.